Distribution and Frequency of Pyrethroid Resistance-Associated Mutations in Host Lineages of the Bed Bug (Hemiptera: Cimicidae) Across Europe - Balvín, Ondřej; Booth, Warren (Journal of medical entomology, 2018)
For over two decades, the bed bug, Cimex lectularius L. (Hemiptera: Cimicidae) has been undergoing a dramatic global resurgence, likely in part to the evolution of mechanisms conferring resistance to insecticides. One such mechanism is knock-down resistance (kdr), resulting from nonsynonymous mutations within the voltage-gated sodium channel (VGSC) gene. To date, three mutations have been identified in C. lectularius, V419L, L925I, and I936F. Using Sanger sequencing, the frequency and distribution of these VGSC mutations across 131 populations collected from the bat-associated and human-associated lineages of C. lectularius found in Europe are documented. All populations from the bat-associated lineage lacked mutations at the three sites. In contrast, the majority of populations associated with humans (93.5%) possessed the mutation at the L925I site. The I936F mutation, previously only reported in Israel and Australia, was found in nine populations spread across several European countries, including the Czech Republic and Switzerland. The high frequency of kdr-associated resistance already reported in C. lectularius and the occurrence and broad geographic distribution of this additional VGSC mutation, questions the continued use of pyrethroids in the treatment of infestations.
Keywords: mutace; Pyrethrins; Animals; rezistence k insekticidům; Bedbugs; Europe; zvířata; Evropa; Insecticide Resistance; pyrethriny; Insecticides; Mutation; štěnice; insekticidy